2019
DOI: 10.1101/lm.048942.118
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention in rat visual category learning

Abstract: A prominent theory of category learning, COVIS, posits that new categories are learned with either a declarative or procedural system, depending on the task. The declarative system uses the prefrontal cortex (PFC) to learn rule-based (RB) category tasks in which there is one relevant sensory dimension that can be used to establish a rule for solving the task, whereas the procedural system uses corticostriatal circuits for information integration (II) tasks in which there are multiple relevant dimensions, precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 60 publications
(76 reference statements)
3
48
0
Order By: Relevance
“…The typical trial sequence contains four phases, a Star phase, Cue phase, Choice phase and Reward phase (Figure 1A). 37,38 Importantly, this trial sequence separates categorization (Cue phase) from decision execution (Choice phase) and feedback processing (Reward phase), a feature that is favorable for neuroscientific approaches like optogenetics and neurophysiological recording. The trial sequence is self‐paced, which ensures the rat is attending to the screen and has adequate time to (a) observe the category stimulus and (b) make a category decision.…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical trial sequence contains four phases, a Star phase, Cue phase, Choice phase and Reward phase (Figure 1A). 37,38 Importantly, this trial sequence separates categorization (Cue phase) from decision execution (Choice phase) and feedback processing (Reward phase), a feature that is favorable for neuroscientific approaches like optogenetics and neurophysiological recording. The trial sequence is self‐paced, which ensures the rat is attending to the screen and has adequate time to (a) observe the category stimulus and (b) make a category decision.…”
Section: Experimental Designmentioning
confidence: 99%
“…Rodents are well suited for determining the neural mechanisms underlying cognitive functions, and although the study of categorization in non‐human animals has heavily relied on pigeons, 28‐34 rats are capable of category learning 35‐42 . We have developed category learning tasks for rats using touchscreens as a foundation for a systematic analysis of the neural mechanisms underlying categorization.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have shown the benefits of long-term memory for learning new information with similar principle (Gerven et al, 2017;Oberauer et al, 2017;Wang et al, 2017). In addition, rule-based learning (combined cues with an abstract principle) has been reported during associative learning both in human and animal studies (Racht-Delatour and Massioui, 1999;Wills et al, 2011;Maes et al, 2017;Broschard et al, 2019). Compared with remembering only separate cues, rule-based learning is more stable with the passing of time and can adjust to various contexts (Hoffmann et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The rise in popularity of touchscreen technology for cognitive behavioral testing in rodent neuroscience research suggests that accumulating knowledge and collaborating through an annual or biennial symposium, twice‐yearly hands‐on training course and through our virtual community on https://touchscreencognition.org/ ensures that common issues can be addressed which can further improve standardized testing. Some of these issues involve optimizing touchscreen systems such as the hardware, 47 and development of new touchscreen tasks which is easily achievable because of the flexibility of the touchscreen systems 15,48,49 . For example, Piantadosi et al 48 have developed a novel multichoice task for assessing cognitive flexibility.…”
Section: The Future Of Rodent Touchscreen Technologymentioning
confidence: 99%